Immunogenicity persistence after four intramuscular triple-dose or standard-dose hepatitis B vaccine in patients receiving methadone maintenance treatment: A 1-year follow-up study in China - Xinyuan Mo; Zhaoyue Men; Linying Gao; Yizhuo Gao; Tian Yao; Yuan Liu; Yuan Yuan; Tongchuan Xue; Fuzhen Wang; Suping Wang; Keke Wang; Xiaofeng Liang; et al. (Human Vaccines & Immunotherapeutics)
Patients receiving methadone maintenance treatment (MMT) elicited poor response and rapid anti-HBs loss after standard hepatitis B vaccination. An optimal hepatitis B vaccination was urgent. A randomized, parallel-controlled trial was conducted in patients receiving MMT from 2019 to 2020, and patients were randomized to receive 3 or 4 doses of 20 or 60 µg of hepatitis B vaccine. Follow-up was extended to 2021, for assessment of 1-year persistence of immunogenicity at month 18. A total of 145 participants completed the 1-year follow-up. From month 7 to 18, the response rates of the IM60 × 4 group, IM20 × 4 group, and IM20 × 3 group decreased from 95.52% (64/67) to 84.09% (37/44), 94.67% (71/75) to 78.72% (37/47), and 89.19% (66/74) to 68.52% (37/54), respectively. No significant differences were observed in the persistence of vaccine-induced responses among the three groups (p = .204). All three hepatitis B vaccine regimens demonstrated comparable declines in anti-HBs levels, with a rapid decrease observed within 1-year of follow-up.Clinical trial registration ClinicalTrials.gov (NCT03962816).https://clinicaltrials.gov/ct2/show/NCT03962816